THE ROLE OF SUNDAY SCHOOL TEACHERS IN CHILDREN'S CHARACTER DEVELOPMENT AT BETHEL INDONESIA CHURCH, HOTEL PELANGI, SIMPANG SELAYANG, MEDAN, 2024 - Saragih, Novita; Karo-Karo, Selamat; Girsang, Dameria; Wiharokusumo, Padriadi; Zalukhu, Esra (Jurnal Ilmiah Akomodasi Agung, 2025)
This study examines the role of Sunday School teachers in shaping children's character through Christian religious education. The objective of this research is to identify the teaching strategies implemented and their impact on children's character development. The study employs a qualitative method with a case study approach conducted at Bethel Indonesia Church, Hotel Pelangi, Simpang Selayang, Medan. Data were collected through interviews, observations, and document analysis. The findings indicate that Sunday School teachers play a crucial role in character formation through role modeling, Bible-based learning, and positive social interactions. Creative teaching methods such as storytelling, role-playing, and interactive group activities have been proven to enhance children's understanding of Christian values. However, challenges such as a lack of training, limited facilities, and varying levels of student participation remain obstacles. It is recommended that churches provide regular training for Sunday School teachers, improve the availability of relevant teaching materials, and develop a more structured curriculum suited to children's growth. Additionally, parental involvement in character education is expected to strengthen learning outcomes. By enhancing the role of Sunday School teachers, this study contributes to the moral and spiritual development of children in Bethel Indonesia Church, Hotel Pelangi, Simpang Selayang, Medan.